Association between skin-to-skin contact post-birth and breastfeeding behaviour: a cross-sectional study of Nigerian women using the 2018 Demographic Health Survey - Maria Pilar Martin; Chinedu U. Obioha; Ogochukwu A. Obioha; Alicia Padron-Monedero (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background The World Health Organisation (WHO) recommends skin-to-skin contact at birth as part of the essential newborn care processes that can help improve breastfeeding behaviours in new mothers. In 2019 Nigeria had the highest number of infant mortalities (270,000 infant deaths), second only to India (522,000 infant deaths). Consequently, the possible benefits of skin-to-skin contact and healthy breastfeeding behaviours to both mother and child cannot be overemphasised. This study seeks to understand the rate of skin-to-skin contact post-birth and how this affects early breastfeeding initiation, breastfeeding duration, and exclusive breastfeeding among Nigerian women. It also seeks to understand if the place of delivery or internet access affects the associations between skin-to-skin contact and breastfeeding behaviours. # Methods Data from the Demographic and Health Survey (2018) on Nigerian women were analyzed, and 19,328 women were included in this study. The association between skin-to-skin contact post-birth (independent variable) and breastfeeding initiation, exclusive breastfeeding, and breastfeeding duration (dependent variables) were analyzed with multivariable logistic regression models adjusted for known confounders. The modifying effects of place of delivery and internet use were also assessed. # Results Nearly 13% of Nigerian women experienced skin-to-skin contact post-birth. The odds of exclusive breastfeeding were higher for women who experienced skin-to-skin contact with their newborns, compared to those that did not (odds ratio, OR=1.24, 95% confidence interval, CI=1.13-1.36). Conversely, the odds of initiating breastfeeding within the first hour of birth (OR=0.87, 95% CI=0.79-0.96) were lower in women who experienced skin-to-skin contact post-birth. There was no association between skin-to-skin contact and breastfeeding duration. Delivering their baby in private hospitals modified the association between skin-to-skin contact and early breastfeeding initiation (OR=3.27, 95% CI=2.33-4.60, P<0.001), as well as the association between skin-to-skin contact and breastfeeding duration (OR=1.56, 95% CI=1.14-2.15, P=0.008) more strongly than delivering their baby in public hospitals. # Conclusions In Nigerian women, skin-to-skin contact post-birth is associated with some breastfeeding behaviours (early initiation and exclusive breastfeeding). However, associations between skin-to-skin contact and breastfeeding behaviours of early breastfeeding initiation and breastfeeding duration may be modified by the place of delivery. Therefore, health interventions to increase skin-to-skin contact practices should target skilled health providers, particularly in public hospitals.